2022
DOI: 10.3389/fimmu.2022.827953
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Omics Study of Familial Lung Cancer: Microbiome and Host Gene Expression Patterns

Abstract: BackgroundInherited susceptibility and environmental carcinogens are crucial players in lung cancer etiology. The lung microbiome is getting rising attention in carcinogenesis. The present work sought to investigate the microbiome in lung cancer patients affected by familial lung cancer (FLC) and indoor air pollution (IAP); and further, to compare host gene expression patterns with their microbiome for potential links.MethodsTissue sample pairs (cancer and adjacent nonmalignant tissue) were used for 16S rRNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Considering COVID-19 severity (requirement of supplemental oxygen or mechanical ventilation) in breast cancer patients, we found a direct relationship with relative abundance of 2021) also report the presence of this genus exclusively in COVID-19 patients admitted to intensive care units. For Parasegitibacter luogiensis and Thermomonas, the higher abundance is likely resulted from opportunistic infections, as Parasegitibacter is associated with soil and skin microbiome (Manus et al, 2020), and Thermomonas is common in air pollution (Chen et al, 2022). This study has some limitations as all samples consist of a mix of nasal and oropharyngeal regions obtained by swabbing.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering COVID-19 severity (requirement of supplemental oxygen or mechanical ventilation) in breast cancer patients, we found a direct relationship with relative abundance of 2021) also report the presence of this genus exclusively in COVID-19 patients admitted to intensive care units. For Parasegitibacter luogiensis and Thermomonas, the higher abundance is likely resulted from opportunistic infections, as Parasegitibacter is associated with soil and skin microbiome (Manus et al, 2020), and Thermomonas is common in air pollution (Chen et al, 2022). This study has some limitations as all samples consist of a mix of nasal and oropharyngeal regions obtained by swabbing.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding Scardovia , Rueca et al (2021) also report the presence of this genus exclusively in COVID-19 patients admitted to intensive care units. For Parasegitibacter luogiensis and Thermomonas , the higher abundance is likely resulted from opportunistic infections, as Parasegitibacter is associated with soil and skin microbiome ( Manus et al, 2020 ), and Thermomonas is common in air pollution ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In normal situation, it should be in a healthy balance, but inhaled carcinogens or hazardous microbes may cause cell mutations and chronic inflammation, leading to cancerogenesis. Microbiome gene expression diversity seemed to be higher than that of their human hosts because individual subjects could have different microbiomes, but all patients shared the same set of human genes, albeit frequently different alleles ( 26 ).…”
Section: Gene Expressionmentioning
confidence: 99%
“…A great number of research studies have indicated that lung microbial communities include bacteria and other non-bacterial organisms, comprising fungi and viruses. SARS-CoV-2 may diffuse in the lung as aerosols, then colonize though pulmonary mucus (Nguyen et al, 2015;Chen et al, 2022). Gherlan et al reported a case that the COVID-19 patient got the entire right lung removed, the direct microscopic detection confirmed A. baumannii, Mucorales, Candida species (Gherlan et al, 2022).…”
Section: Pulmonary Bacterial and Fungal Infections Coexist With Covid-19mentioning
confidence: 99%
“…A great number of research studies have indicated that lung microbial communities include bacteria and other non-bacterial organisms, comprising fungi and viruses. SARS-CoV-2 may diffuse in the lung as aerosols, then colonize though pulmonary mucus ( Nguyen et al., 2015 ; Chen et al., 2022 ). Gherlan et al.…”
Section: Pulmonary Bacterial and Fungal Infections Coexist With Covid-19mentioning
confidence: 99%